Inventory of Non-timber forest Products through Adaptive Cluster Sampling - Mishra, C. K.; Ramakrishna Naidu, G. (Indian Forester, 2014)
Inventory of the growing stock based upon stratified random sampling has been applied to estimate the timber resources in the forests. This method cannot give precise estimate of NTFPs yielding herbs and shrubs with patchy and clustered distribution. Our field study in the forests of Chittoor district of Andhra Pradesh indicates that inventory of a shrub named Decalepis hamiltonii, an important NTFP tuber species is best estimated with the help of 'Adaptive Cluster Sampling' applying the Horvitz - Thompson estimator. This method can be replicated for other species with similar distributions. Precise inventory coupled with productivity assessment is required to standardize management prescriptions.